Symbol and Meaning of Kapata Oral Tradition Texts in Central Maluku - Letlora, Prihe Slamatin (ELS Journal on Interdisciplinary Studies in Humanities, 2018)
The purposes of this research were (1) to reveal the kinds of symbols that applied in the texts of Kapata in Central Maluku and (2) to map out the meanings of the symbols. The data of this research was taken from texts of Kapata in Saparua Island, Central Maluku. The texts were obtained from field research through the process of observation, library research and interview. All obtained data were analyzed with descriptive qualitative analysis. The results of this research explained that (1) in Saparua Island, types of symbols found were Lexical Symbols (Noun and Adjective), Phrasal Symbols (Verb Phrase and Noun Phrase), Clausal Symbol (Dependent Clause) and Sentential Symbol; and (2) it is obviously seen that Kapata generally contained either denotative or denotative - connotative meanings.